Amendments to the General Corporations Law in Matters of Corporate Name, Corporate Purpose, and Powers and Attributions of the Chief Executive Officer by the Legislative Decree 1332 that Facilitates the Incorporation of Companies through the Business Development Centers - Peró Mayandía, Mariano (2017)
The recently promulgated Legislative Decree No. 1332 aims to promote business formalization by facilitating the incorporation of companies. To this end, it promotes the establishment of the Business Development Centers and amends various articles of the General Corporations Law in matters of corporate name, corporate purpose, and powers and attributions of the Chief Executive Officer.In this article, the author analyzes the new regulations on Business Development Centers and comments on the recent amendments to the General Corporations Law, in order to determine their effects and suitability.